Decreased plasma levels of soluble receptor for advanced glycation endproducts (sRAGE) in patients with nonalcoholic fatty liver disease - ATUĞ, ÖZLEN; YILMAZ, YUSUF (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Objectives: Levels of soluble receptor for advanced glycation endproducts (sRAGE) have been linked to several components of the metabolic syndrome. We tested the hypothesis that plasma levels of sRAGE may be associated with non-alcoholic fatty liver disease. Design and methods: We enrolled subjects with definite nonalcoholic steatohepatitis (NASH, n=40), borderline NASH (n=8), simple fatty liver (n=9) and healthy controls (n=14). Plasma levels of sRAGE were measured by ELISA. Results: Concentrations of sRAGE were significantly lower in patients with definite NASH (1080 +/- 392 pg/mL, P<0.01) and borderline NASH (1050 +/- 278 pg/mL, P<0.05) compared to controls (1480 +/- 387 pg/mL). Levels of sRAGE were significantly and inversely correlated with ALT (r=-0.30, P<0.05) and AST (r=-0.23, P<0.05). Conclusion: Plasma levels of sRAGE are significantly reduced in definite and borderline NASH. (c) 2009 The Canadian Society of Clinical Chemists. Published by Elsevier Inc. All rights reserved.
Keywords: Fatty liver; Biological markers; Receptor for advanced glycation endproducts (RAGE); Enzyme-linked immunosorbent assay; END-PRODUCTS AGES; INSULIN-RESISTANCE; SERUM-LEVELS; RAGE; FORM; PATHOGENESIS; GALECTIN-3; PROTEIN